Searching The Shortest Route to Visit Tourism By Using The Greedy Algorithm - Hardy Priyatno Ambarita; Jonson Manurung (Putaka Timur Publisher, 2021)
Technological developments make any information can be spread in a short time. Technology can also be used to advertise any place, business, product. Technological developments cannot be separated from every activity carried out by humans, one of which is the determination of the nearest tourist attraction. Tourism is a place for relaxing and can visit until the time desired by visitors. From the above explanation, it can be said that a destination is a place that can be visited by foreign and domestic tourists. Searching for the shortest route is an obstacle that is often faced by every seeker of alternative paths to reach their destination faster. Several other methods can solve the problem of finding a route. One method that can solve this problem is using the heuristic search method. One of them is the Greedy Best-first search algorithm. This algorithm works by taking into account the approximate cost. Selecting the next best node is done by examining the estimated cost obtained using a heuristic function. Given the problems above, it is necessary to make a solution to determine the shortest route to assist tourists in choosing the route to be traversed in tourism in Deliserdang.